Behind the Reasons: The Relationship Between Adolescent and Young Adult Mental Health Risk Factors and Exposure to Season One of Netflix’s 13 Reasons Why - Evans, Jabari Miles; Lauricella, Alexis R.; Cingel, Drew P.; Cino, Davide; Wartella, Ellen Ann (Frontiers in Human Dynamics, 2021)
With increasing media choice, particularly through the rise of streaming services, it has become more important for empirical research to examine how youth decide which programs to view, particularly when the content focuses on difficult health topics such as suicide. The present study investigated why adolescents and young adults chose to view or not view season 1 of 13 Reasons Why and how individual-level variables related to adolescents’ and young adults’ viewing. Using survey data gathered from a sample of 1100 adolescents and young adult viewers and non-viewers of the series in the United States, we examined how participants’ resilience, loneliness, and social anxiety related to whether participants viewed the first season. Our descriptive results indicate that adolescents who watched the show reported that it accurately depicted the social realities of their age group, they watched it because friends recommended it, and they found the subject matter to be interesting. Non-viewers reported that they chose not to view the show because the nature of the content was upsetting to them. In addition, results demonstrated that participants’ social anxiety and resilience related to participants’ viewing decisions, such that those with higher social anxiety and higher resilience were more likely to report watching season 1. Together, these data suggest that youth make intentional decisions about mental health-related media use in an attempt to choose content that is a good fit for based on individual characteristics.